Infectious scleritis: a comprehensive narrative review of epidemiology, clinical characteristics, and management strategies - Hamidreza Ghanbari; Masoud Rahimi; Ali Momeni; Kiana Hassanpour; Nikoo Bayan; Karen E. Lee; Alex Hansen; Ali R. Djalilian; Christopher J. Rapuano; Mohammad Soleimani (Therapeutic Advances in Ophthalmology, 2025)
This study aims to provide an update on infectious scleritis (IS). A comprehensive search was conducted using Google Scholar, Scopus, and PubMed. IS is a rare but critical condition that presents significant diagnostic challenges and often leads to poor visual outcomes. It accounts for approximately 5%–10% of scleritis cases and warrants significant attention due to its delayed diagnosis. Ocular surgery is the primary contributor to IS, accounting for a substantial proportion of cases ranging from 58% to 83%, followed by trauma contributing to approximately 10% of cases. IS can be caused by various microorganisms, including bacteria (86%–87%), fungi (11%–13%), viruses, and parasites. Conjunctival hyperemia is a prevalent manifestation in approximately 98% of IS cases, while scleral necrosis is observed in around 93% of cases. Distinguishing IS from inflammatory scleritis before initiating steroid treatment is crucial. Surgical debridement of infected tissue, accompanied by appropriate topical and systemic antibiotic therapy significantly improves treatment outcomes by removing infected tissue and reducing the infection burden. Early surgical intervention markedly increases the likelihood of preserving the eye globe in severe cases. Risk factors for poor visual outcomes include poor visual acuity at presentation, associated endophthalmitis, keratitis, fungal etiology, and medical therapy without surgical debridement. Early diagnosis of IS is crucial as the disease can progress rapidly and lead to vision loss. While bacterial infections are the most common etiology of IS, the prognosis is particularly poor in cases of fungal IS. Surgical interventions, when combined with appropriate medical treatment, improve outcomes.